A Statistical Approach in Designing an RF-Based Human Crowd Density Estimation System - Fadhlullah, S. Y.; Ismail, Widad (SAGE Publications, 2016)
The study of human crowd density estimation (H-CDE) using radio frequency is limited due to the nature of wireless medium and the advancement of visual-based systems.There were two statistical methods, namely, One-Way Analysis of Variance and Design of Experiment applied in designing the H-CDE system. One-Way Analysis of Variance is used to investigate the difference in signal attenuation between dynamic and static crowds. The Design of Experiment is utilized to identify significant crowd properties that affect wireless signal propagation.The significant factors were later trained into theH-CDE algorithmfor the purpose of estimating the human crowd density in a defined sector. A sector comprising three placements of 2.4GHz ZigBee wireless nodes continuously reported the received signal strength indicator to the main node. The results showed that the H-CDE system was 75.00% and 70.83% accurate in detecting the low and medium human crowd density, respectively. A signal path loss propagation model was also proposed to assist in predicting the human crowd density.The human crowd properties verified by using the statistical approach may offer a new side of understanding and estimating the human crowd density.